Rāja yoga : being lectures by the Swami Vivekananda, with Patanjali's aphorisms, commentaries and a glossary of terms /: being lectures by the Swami Vivekananda, with Patanjali's aphorisms, commentaries and a glossary of terms. (2018) - Swami, Vivekananda, 1863-1902
No abstract available